Conference ECCO news and controversies - Żuchowska-Vogelgesang, Beata; Krzemieniecki, Krzysztof; Pawlicki, Marek; Ziobro, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
The twelfth European Conference of Clinical Oncology took place in Lisbon, Portugal between 20-26 October 2001. Many outstanding cancer centers presented results of their recent studies. The issues dedicated to breast cancer were dominated by early breast cancer management. Clinical indications for conservatory breast surgery, the biopsy of sentinel lymphonode and adjuvant radiotherapy in this group of patients were broadly discussed. Megadose chemotherapy in poor-prognosis breast cancer patients were critized. Controlled clinical studies on use of taxoides and herceptin adjuvant treatment was presented. A several new drugs under investigation and preliminary results especially of Iresa, Tarceva and RO31-7453 were presented. Clinical rationals for adjuvant chemotherapy in early stage of ovarian cancer and possible impact of Ovarex, monoclonal antibody treatment on survival in patients with high level of CA 125 antigen were discussed. Extended combinations of platinum derivatives, paclitaxel, gemcytabina and topotecan were evaluated. New generation of anti-cancer drugs like ZD 04 73, BBR 34 64 and its usfulne in ovarian cancer treatment were presented. The role of the biopsy of sentinel lymphonode in malignant melanoma staging and technical problems of this procedure dominated many congress presentations. Data on adjuvant interferon therapy and treatment of disseminated melanoma with interleukine-2 and ceplene combination were given. The role of systemic treatment and optimal chemotherapy regimen for non-small cell lung cancer (NSCLC) were discussed. The recent studies on use of Herceptin in lung cancer were introduced. The results of second line chemotherapy in NSCLC for first line responders were debated. Endobronchial radiotherapy and its clinical benefits were introduced. New agents in NSCLC, especially Alimta, Iressa, BBR 3664 were demonstrated. Promising, preliminary results of gastrointenstined stromal tumors (G/ST) treatment with Glivec were announced. New perspectives of ecteinascidin therapy for advanced soft tissue sarcomas were discussed. ECCO-12 was stimulating international forum for exchange the recent studies data and presentation of state of art in clinical oncology in year 2001.